A study on craniometric analysis of adult human skulls in Telangana population - DR. SAMATA ROSHINI PADALA M.D,; MS. NAUSHEEN KHAN, (International Journal of Pharma and Bio Sciences, 2017)
Craniometry is the scientific measurement of various dimensions of bones of the skull useful for anthropometry and forensic practice in segregation of age, gender, stature, race, etc. of unknown persons. The present study was conducted in Osmania Medical College, Hyderabad, Telangana, India consisting of fifty (31male and 19 female) dry adult human skulls of Telangana population collected from the Department of Anatomy and Forensic of three different Medical Colleges of Hyderabad. Cranial indices are useful for deciding racial and gender differences. The aim of the study was to determine sexual dimorphism of skull by using craniometric data. Therefore, measurements of maximum cranial length, breadth and height were taken using sliding Vernier Calipers and cranial indices of all the skulls were determined. The mean cranial length in male and female skulls was 17.66cm, in male it was 17.92cm and in female 17.1cm. The mean cranial breadth in male and female was 13.2cm, in male and female 13.4cm and 12.9cm respectively. The mean cranial index of male and female skulls examined was 75.21% in male 75.32% and in female 75.42%. The results in the present study showed no difference in cranial indices of male and female skulls which indicates less sexual dimorphism. In the present study, depending on the mean cranial index, n = 21 (42%) skulls belong to dolicocephalic, n = 24 (48%) to mesocephalic, n = 5 (10%) to brachycranic and no skull belong to hyperbrachycephalic. The result of this study will be of importance in forensic medicine, anthropology and in genetics. It has further application in clinical specialities such as plastic surgeries and oral surgery with craniofacial deformities